2020
DOI: 10.1111/jcmm.16055
|View full text |Cite
|
Sign up to set email alerts
|

Nepetin inhibits osteoclastogenesis by inhibiting RANKL‐induced activation of NF‐κB and MAPK signalling pathway, and autophagy

Abstract: Joint replacement is a common surgical procedure for the terminal stages of degenerative joint diseases including rheumatoid arthritis and osteoarthritis. 1 Despite advances in surgical procedures and prosthetic material, peri-prosthetic osteolysis and the resulting aseptic loosening remains a major complication leading to implant failure. 2 Titanium (Ti)-based biomaterials are by far the most commonly used prosthetic implants due to their superiority in load-bearing applications and excellent mechanical stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…6B ). One previous study revealed that TRAF6 is the major E3 ubiquitinligase that causes the K63-mediated ubiquitination of Beclin-1 [ 27 , 28 ], were confirmed by the results in the present study. And we found that knockdown of TRAF6 expression reduced K63-mediated ubiquitination of Beclin-1 (Fig.…”
Section: Resultssupporting
confidence: 92%
“…6B ). One previous study revealed that TRAF6 is the major E3 ubiquitinligase that causes the K63-mediated ubiquitination of Beclin-1 [ 27 , 28 ], were confirmed by the results in the present study. And we found that knockdown of TRAF6 expression reduced K63-mediated ubiquitination of Beclin-1 (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Studies shows anti-carcinogenic potential of various phytochemicals such as carotenoids, chlorophyll, flavonoids, indole, isothiocyanate, polyphenolic compounds, protease inhibitors, sulfides, and terpens [37]. Natural active flavonoid that are abandoned in various plants has been proved to exhibit multiple biological effects possessing anti-apoptotic, anti-inflammatory, anti-oxidant and anti-cancer properties [70]. The specific mechanisms of action of most phytochemicals in cancer prevention are not yet clear but appear to be varied [71].…”
Section: Resultsmentioning
confidence: 99%
“…Various osteoclast markers reduced in the SR group, including RANK, TRAF6, NFATc2, c-Fos, and some proteases related to bone resorption, such as MMP-9, MMP-14, and CTSK. These proteases could degrade extracellular matrix protein, including collagen and elastin, break intercellular connections, and promote cell development and migration [ 15 , 35 , 38 , 39 , 40 ] In addition, orthodontic tooth movement at the pressure side of the first molars was inhibited in the SR group, according to the analysis of 3D reconstruction with micro-CT. The inhibition of tooth movement might result from the fact that SR significantly enhances the micro-architecture of trabecular bone by attenuating osteoclast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the NF-κB pathway has been proven to play an important role in autophagy, and the strong link between autophagy and osteoclastogenesis is being increasingly appreciated [ 15 ]. Autophagy, a highly conserved catabolic process in eukaryotes, is responsible for phagocytosing and degrading damaged organelles or aged proteins via the lysosomal pathway.…”
Section: Introductionmentioning
confidence: 99%